Identifying Key Determinants of Islamic Customer Perceived Value: A Mixed-Method Study - Yayuk Sri Rahayu; Fitriyah Fitriyah; Guntur Kusuma Wardana (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The concept of customer perceived value is crucial for businesses to understand consumer behavior and gain a competitive edge; however, research on Muslim consumers remains scarce. This study seeks to identify the indicators and factors that shape Islamic customer perceived value, particularly within tertiary education institutions. A mixed-methods approach was employed, beginning with qualitative research using focus group discussions and interviews, followed by quantitative analysis through principal component analysis. The focus groups included students, lecturers, and experts, while 118 respondents completed the questionnaires. The findings uncovered 21 indicators and 6 key factors, namely: Islamic academic standards, Islamic attitudes, Islamic performance, Islamic physical attributes, Islamic organizational values, and Halal food and beverage offerings. These results advance the understanding of Islamic marketing and provide valuable insights for universities when formulating marketing strategies aligned with Islamic principles.